I spy love : a book of picture riddles - Marzollo, Dan; Wick, Walter 1953-; Marzollo, Dave (New York Cartwheel Books, an imprint of Scholastic Inc., 2024)
"Love is in the air with a brand-new I Spy book! Can you find Cupid and his bow, a groom with a bride, wedding rings, babies, pets, and stuffed animal hugs? How many different hearts can you search and find? There are hearts on dice, hearts on cards, and hearts on coins. Look for rainbow hearts and zebra hearts. Can you even spot a heart way up in the sky?"--
Ages 4-8 years
Grades 2-3
115310
Keywords: Picture puzzles -- Juvenile literature; Riddles, Juvenile; Juvenile Fiction -- Valentine's Day -- Holidays & Celebrations; Juvenile Fiction -- Concepts -- Counting & Numbers; Picture puzzles; Riddles